2014
DOI: 10.3109/00365521.2014.928902
|View full text |Cite
|
Sign up to set email alerts
|

Antibody and cell-mediated immune response to whole virion and split virion influenza vaccine in patients with inflammatory bowel disease on maintenance immunosuppressive and biological therapy

Abstract: Split virion vaccines seem to be more effective than whole virion vaccines. Measuring the antibody responses is worthwhile in patients treated with immunosuppressants to determine the efficacy of influenza vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The 2 systematic reviews in healthy adults, and the 10 other studies in adults with IBD showed no serious adverse events associated with the use of inactivated influenza vaccine. 88,89,[91][92][93][94][95][96][97][98][99][100] The evidence for efficacy and safety were anchored to the general population. The CoE for efficacy remained moderate because studies suggesting reduced immunogenicity in patients with IBD showed that the European Union Committee for Medicinal Products for Human Use criteria for effective immunogenicity were met in the majority of patients.…”
Section: Influenzamentioning
confidence: 99%
“…The 2 systematic reviews in healthy adults, and the 10 other studies in adults with IBD showed no serious adverse events associated with the use of inactivated influenza vaccine. 88,89,[91][92][93][94][95][96][97][98][99][100] The evidence for efficacy and safety were anchored to the general population. The CoE for efficacy remained moderate because studies suggesting reduced immunogenicity in patients with IBD showed that the European Union Committee for Medicinal Products for Human Use criteria for effective immunogenicity were met in the majority of patients.…”
Section: Influenzamentioning
confidence: 99%